2011
DOI: 10.1016/j.jsat.2010.11.005
|View full text |Cite
|
Sign up to set email alerts
|

College alcohol citations result in modest reductions in student drinking

Abstract: College students who are cited for violating campus alcohol policy are often fined or sanctioned to complete an intervention or public service. While some interventions have been found efficacious for mandated students, it is possible that being cited for an alcohol-related incident alone may be sufficient to reduce alcohol consumption. The purpose of this study was to investigate the course of alcohol consumption patterns following a citation for an alcohol policy violation. Participants were college students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 21 publications
7
26
0
Order By: Relevance
“…Students who violate campus alcohol policies tend to be riskier drinkers (Fromme & Corbin, 2004; LaBrie, Tawalbeh, & Earleywine, 2006), and are often required to participate in mandated interventions (Barnett & Read, 2005). Many of these students are motivated to change and some will reduce their drinking behavior, even prior to intervention (Barnett, Goldstein, Murphy, Colby, & Monti, 2006; Carey, Henson, Carey, & Maisto, 2009; Hustad et al, 2011; Morgan, White, & Mun, 2008; White, Mun, & Morgan, 2008; Wray, Simons, & Dvorak, 2011). However, not all students change.…”
Section: Introductionmentioning
confidence: 99%
“…Students who violate campus alcohol policies tend to be riskier drinkers (Fromme & Corbin, 2004; LaBrie, Tawalbeh, & Earleywine, 2006), and are often required to participate in mandated interventions (Barnett & Read, 2005). Many of these students are motivated to change and some will reduce their drinking behavior, even prior to intervention (Barnett, Goldstein, Murphy, Colby, & Monti, 2006; Carey, Henson, Carey, & Maisto, 2009; Hustad et al, 2011; Morgan, White, & Mun, 2008; White, Mun, & Morgan, 2008; Wray, Simons, & Dvorak, 2011). However, not all students change.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, students in the ‘Bad Incident’ group were more likely to respond to the BA session (38% reported lower risk drinking) than those in the ‘Why Me?’ and ‘So What?’ groups (6% and 4%, respectively). Considered in the context of research indicating that a significant subset of mandated students reduce their alcohol use on their own prior to intervention or that they require very little additional intervention (Carey et al, 2009; Hustad et al, 2011; Morgan, White, & Mun, 2008), these findings suggest that a peer-led brief advice session may be an appropriate intervention for a considerable number of mandated students who are light drinkers and/or have significantly reduced their use as a result of the referral incident. Indeed, there has also been increased understanding of what aspects of the referral incident can contribute to these reductions.…”
Section: Discussionmentioning
confidence: 95%
“…Pre-intervention reductions were also noted in a sample of students mandated for minor infractions, with greater reductions associated with heavier drinkers and those with greater readiness to change and pre-sanction consequences (Carey et al, 2009). Finally, one study (Hustad et al, 2011) found heavier drinking rates on the sanction day compared with the typical pattern and slight reductions for the 2 weeks post-sanction, though drinking levels remained above hazardous levels for both men and women.…”
Section: Introductionmentioning
confidence: 97%
“…brief motivational interventions (BMI), cognitive-behavioral skills, and norms clarifications; Cronce & Larimer, 2011; Larimer & Cronce, 2002; 2007; NIAAA, 2002), study findings from mandated samples tend to be less robust as compared to their non-mandated peers. In general, research with mandated samples has demonstrated greater reductions following BMIs among heavier drinkers (LaBrie, Lamb, Pedersen, & Quinlan, 2006; LaBrie, Thompson, Huchting, Lac, & Buckley, 2007) and modest post-sanction effects in lighter drinkers (Borsari et al, 2012; Hustad et al, 2011). However, studies with mandated students tend to report smaller decreases (and occasionally even increases) in drinking behaviors and smaller effect sizes when drinking reductions are detected (e.g., Carey, Henson, Carey, & Maisto, 2009; Cimini et al, 2009; Doumas, Workman, Smith, & Navarro, 2011; Hustad et al, 2014; LaBrie et al, 2006).…”
Section: Introductionmentioning
confidence: 99%